2007
DOI: 10.1088/0957-4484/18/9/095709
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic conductance calculation of atomic-scale nanowires of Au and Co

Abstract: Ballistic conductance calculations on infinite one-atom zigzag chains of Co and Au, and multi-atom Au nanowires, were computed using the Landauer–Büttiker formalism within the local-density approximation (LDA). In the cobalt case, the majority spin channel exhibits quantized conductance, but because of the close spacing of the d levels, the minority channel does not. The calculated conductance is somewhat larger than what is observed. We suggest that the discrepancy is an indication that the Landauer–Büttiker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The electronic contribution to the conductance behavior has not been investigated in detail except for the linear nanowire. 8,9,13,36 In this section, we present correlation between electronic structure and conductance behavior of 2D For linear NW, the transmission at the Fermi level shows a jump from 3G o to 1G o as shown in Fig. 5(a), in agreement with, the earlier reports on conductance calculations.…”
Section: Conductivitysupporting
confidence: 86%
“…The electronic contribution to the conductance behavior has not been investigated in detail except for the linear nanowire. 8,9,13,36 In this section, we present correlation between electronic structure and conductance behavior of 2D For linear NW, the transmission at the Fermi level shows a jump from 3G o to 1G o as shown in Fig. 5(a), in agreement with, the earlier reports on conductance calculations.…”
Section: Conductivitysupporting
confidence: 86%
“…Gold SACs also have great potential in applied fields such as nanoelectronics. Many experimental [1][2][3][4][5][6][7][8][9][10] and theoretical [11][12][13][14][15][16][17][18][19][20][21][22][23][24] studies have been carried out to explain the SAC formation and its electrical characteristics. Using density-functional theory (DFT) simulations, it was found that during the nanowire elongation, the arrangement of the gold atoms changes from three-dimensional (3D) phases to a variety of two-dimensional (2D) phases and finally to SACs, which elongate gradually from one up to about nine atoms in the chain.…”
Section: Introductionmentioning
confidence: 99%
“…To verify this interpretation, many theoretical studies have been published to explain the structural changes that occur during gold NW elongation and determine the effect of these configurations on the conductance [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Indeed, it was found that during the elongation, the arrangement of the gold atoms changes from three-dimensional (3D) phases to a variety of two-dimensional (2D) phases and finally to SACs, which elongate gradually from one up to about nine atoms in the chain.…”
Section: Introductionmentioning
confidence: 99%